A Low Dropout Voltage Regulated Bulk-driven CMOS Current Mirror - Nutthawut Minwong; Kriangkrai Sooksood; Apinunt Thanachayanont (My University, 2016)
Novel bulk-driven current mirror (CM) and bulk-driven cascode CM are presented in this paper. Bulk-driven technique is employed to overcome a threshold voltage limitation. Proposed circuits operate at 1 V power supply. By using a negative feedback, high accuracy input and output transfer characteristic over wide current range is achieved. The proposed circuits are simulated using a 0.18 μm CMOS technology. The headroom voltage is 0.11 V for the proposed bulk driven CM and 0.16 V for the proposed bulk driven cascode CM.
Keywords: Cascode; Current mirror; Analog and Mixed-Signal Circuit Design